PENERAPAN MODAL SOSIAL PADA KEBERHASILAN PROGRAM PEMBIAYAAN BERBASIS KELOMPOK SEBAGAI UPAYA PENANGGULANGAN KEMISKINAN (STUDI KASUS PADA KOPERASI KELOMPOK HUMANIORA POKMAS MANDIRI, KANTOR CABANG DELI SERDANG) - Elvira Agustina (Universitas Islam Negeri Sumatera Utara, 2021)
Materials/goods collateral is the biggest obstacle for MSMEs from poor families to obtain banking services and financing facilities.Social capital as a solution applied to group-based financing programs. This study attempted to analyze the application of social capital to the success of group-based financing programs in poverty alleviation efforts at The Humaniora Group Cooperation of Pokmas Mandiri at Deli Serdang Branch. The subjects of this study consisted of observer informants from The Humaniora Group Cooperation of Pokmas Mandiri, and the perpetrator informants namely members of the cooperation. This research is a field research using a qualitative approach. Data collections techniques used in this study were in-depth interviews, documentation, observation and review of literature. Based on the results, it was obtained that 1) The application of group-based financing programs has been modified to the conditions and needs of the society in Deli Serdang Regency, both from the social, economic and cultural of the society; 2) The application of social capital in the group-based financing program is considered very effective and efficient for The Humaniora Group Cooperation of Pokmas Mandiri in assessing and deciding the eligibility of members, through trust, participation, networks and social norms as assessment characteristics; 3) the success of group-based financing in reducing poverty can be seen through evaluation and direct interviews with members using family prosperity as indicators which is applied by The Humaniora Group Cooperation of Pokmas Mandiri, that the condition of members before and after getting a loan changes, not only increases the standard of living and economy of cooperation’s members, but also has an impact on their quality of life.